THE MEDIATING ROLE OF JOB SATISFACTION AND PROFESSIONAL COMMITMENT IN ENHANCING THE PERFORMANCE OF FEMALE LECTURERS - Novita, Novita; Fatkhurahman, Fatkhurahman; Priadana, Sidik; Tri Juniarti, Atty (Jurnal Riset Bisnis dan Manajemen, 2025)
The role of female lecturers in education is very important and has a significant impact, female lecturers bring a unique gender perspective to learning and research, which is often underrepresented. The performance of female lecturers is an interesting topic to discuss because it involves various factors related to academic productivity, gender challenges, and social roles. This study aims to convince the impact of family social support and encouragement on happiness and reliable commitment and its implications on the ability of female lecturers in large schools in Riau Province. Using a survey method with an illustration of 220 female lecturers who are married with a proportional random sampling technique, information is combined using a questionnaire and analyzed using SEM analysis equipment. The results of the study convince that family social support and encouragement have an important influence on happiness and reliable commitment and have important implications for the ability of female lecturers.